A Systematic Review of the Microbial Landscape of Diabetic Foot Ulcers in Uganda - Makeri, Danladi; Eilu, Emmanuel; Odoki, Martin; Agwu, Ezera (Informa UK Limited, 2024)
Background Diabetes is a growing health concern globally. Poorly managed diabetes may result in diabetic foot ulcers (DFU), which can become a source of chronic infection known as diabetic foot infections. The increasing trend of diabetes in Uganda speaks to the potential for diabetic foot ulcers which may eventually become infected and their attendant impact on the quality of life of diabetic patients. This review assesses the microbial diversity of DFUs in Uganda, aiming to guide treatment and identify research gaps. Main Body of the Abstract We searched PubMed, Scopus and Embase for studies conducted in Uganda that reported isolating microorganisms from diabetic foot ulcers. Following the preferred reporting items for systematic reviews and meta-analysis (PRISMA), we included two eligible studies that reported isolating 122 bacteria spread across eleven (11) species using swab samples and conventional culture methods. Significant isolates included World Health Organization priority pathogens including: Enterobacter specie, Staphylococcus aureus, Klebsiella pneumoniae, and Acinetobacter specie. Methicillin resistant Staphylococcus aureus (MRSA) constituted 33.3% of Staphylococci species and 26% of all bacterial isolates while extended-spectrum beta-lactamase producing Escherichia coli and Klebsiella specie constituted 14.29% of total microbial isolates. Most bacteria showed susceptibility to Imipenem, Vancomycin, Ciprofloxacin, and Clindamycin, but resistance to Cotrimoxazole and Ampicillin was noted. Short Conclusion We conclude that data on the microbiology of DFUs in Uganda is scarce; however, the bioburden of DFUs in the country is similar to those in other parts of the world, and MRSA poses a challenge to antibiotic therapy. Consequently, the continued use of swab samples and conventional culture and sensitivity methods may limit the isolation, identification, and presentation of other important isolates. We recommend characterization of bacterial isolates to better understand their genetic makeup, and the development of a national guideline for managing diabetic foot infections.